The effect of desertification on the phenomenon Sand dunes in Maysan Governorate - ., Sabah baji (Al-Adab Journal, 2015)
Formed environment in carryover first configuration of the human obsession of fear, and today at the beginning of the second decade of the millennium has become a fear compound of the environment and the source of this fear composite one, not merely for the misuse of the components of environmental, which contributed to the contamination by modern industries with outputs Altlutah high, In light of the investment is not rational to environmental resources, reliance on manufactured goods increased increased dramatically included food and Drug Administration, proposing to the environment vast quantities of pollutants that affect human health After that it was the human victim of the environment has become the latest victim has been shifted to exploit its destructive and not Tschara, nor we can deny the significant benefits achieved by human use of nuclear energy in many fields such as medicine, energy and others, but the irrational use in the production of weapons of mass destruction and alternative energy, and let him waste the real killer is threatening the environment and man together. Since this problem took a growing, if it continues to level the Tigris River to decline, and that means dry soil and the formation of sand dunes, as well as the sand dunes caused by the draining of the marshes as well as natural and human factors, which highlights the importance of this research is to identify and draw forms the surface of the earth and to know its structure and nature sedimentary components